Changes in the Practice of Contraceptive Prevalence - An Observational Study (Bangladesh Medical Journal, 2009)
Family planning is an essential tool for reducing fertility rate. An increase in contraceptive prevalence rate results in reduction of population growth, which in turn contributes significantly to the improvement of people's health. It is a cross-sectional, descriptive type, observational study done during April-July 2007 in a large Medical Centre. Reproductive history was used as research instrument for data collection. The present study aimed at exploring Contraceptive prevalence and related issue among service holder and regulation of fertility among them. Two thirty one (231) women (childbearing age ) were selected randomly to find out their contraceptive prevalence. Eighty four (n=197) percent women need family planning service.Among them 87.82 percent (N-173) of the respondents use any method of contraception. 79.76 %( N-138) women use modern method and 20.23 percent( N-35) women use natural method .Thirty three (33.53 %) percent couple practice barrier method, twenty two(22.54%) percent use oral pill, female sterilization is 9.25 percent, injectable (DMPA) 5.78 percent, 7.97 percent mixed method .There is progressive decline in oral pill use from 55% to 26%. Fertility rate, menstruation regulation is lower among servicing women. Education, empowerment and social position of women help to reduce fertility.   DOI: 10.3329/bmj.v37i1.3601 Bangladesh Medical Journal 37(1) 2008 10-14